The Future of Humanities Research in an Inter(Multi, Trans)Disciplinary Context - Žic Fuchs, Milena (Array, 2011)
In the context of future developments in EU policy and funding, we are witnessing the resetting of research agendas and the bridging of gaps between disciplines and research domains. Within the resetting of research agendas the position of the Humanities (and Social Sciences) is being redefined with special reference to how knowledge is created, structured, articulated and used. In this context the buzz word "innovation" is seen as implying new ways of interpreting facts and integrating them into wider networks of knowledge. "Innovative knowledge" helps bridge the gap between the hard and the soft sciences and also provides necessary links to society. New "cultures of knowledge" growing out of interdisciplinary research can be seen as one of the most innovative facets of future research results.